Izboljševanje kakovosti oskrbe bolnikov - Kersnik, Janko (Medicinski razgledi, 1998)
The article defines and explains some terms and concepts of quality assurance and quality improvement of health care.
Keywords: Quality assurance, health care; zdravstveno varstvo; Quality of health care; zdravstvena oskrba; bolniki; kvaliteta